(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Authors of article consider hypertext signs of the art text, analyze key parameters of the hypertext as nonlinear structure in the virtual environment. They do attempt to establish connection of the hypertext with postmodernist poetics, investigate an intertextuality and multimedia of the hypertext. Initial thought is the statement that the hypertext technology gives the chance to submit any text as structure therefore authors of article pay attention to the analysis of essence and features of hypertext technology. Comparison of structure of the hypertext and post-modernist text allows to consider after R. Bart any text as intertext. The ratio of the hypertext and intertextuality is analyzed for detection of specifics of the hypertext. According to authors of article, the intertextuality is based on «idea of dialogue» of M.M. Bakhtin. The main attention is paid to the hypertext space of Olzhas Suleymenov allowing to include the poet in a context of world culture.